Refractoriness in human atria: Time and voltage dependence of sodium channel availability. (December 2016) - Skibsbye, Lasse; Jespersen, Thomas; Christ, Torsten; Maleckar, Mary M.; van den Brink, Jonas; Tavi, Pasi; Koivumäki, Jussi T.
Abstract: Background: Refractoriness of cardiac cells limits maximum frequency of electrical activity and protects the heart from tonic contractions. Short refractory periods support major arrhythmogenic substrates and augmentation of refractoriness is therefore seen as a main mechanism of antiarrhythmic drugs. Cardiomyocyte excitability depends on availability of sodium channels, which involves both time- and voltage-dependent recovery from inactivation. This study therefore aims to characterise how sodium channel inactivation affects refractoriness in human atria. Methods and results: Steady-state activation and inactivation parameters of sodium channels measured in vitro in isolated human atrial cardiomyocytes were used to parameterise a mathematical human atrial cell model. Action potential data were acquired from human atrial trabeculae of patients in either sinus rhythm or chronic atrial fibrillation. The ex vivo measurements of action potential duration, effective refractory period and resting membrane potential were well-replicated in simulations using this new in silico model. Notably, the voltage threshold potential at which refractoriness was observed was not different between sinus rhythm and chronic atrial fibrillation tissues and was neither affected by changes in frequency (1 vs. 3 Hz). Conclusions: Our results suggest a preferentially voltage-dependent, rather than time-dependent, effect with respect to refractoriness at physiologically relevant rates in human atria. However, as the resting membrane potential is hyperpolarized in chronic atrial fibrillation, the voltage-dependence of excitability dominates, profoundly increasing the risk for arrhythmia re-initiation and maintenance in fibrillating atria. Our results thereby highlight resting membrane potential as a potential target in pharmacological management of chronic atrial fibrillation. Highlights: Maximum upstroke velocity of action potential depends strongly on resting membrane potential. A new in silico human atrial cell model based on both in vitro sodium current data and ex vivo action potential data. The threshold potential of refractoriness was similar in SR and cAF tissues, and at both pacing frequencies (1 vs. 3 Hz). Refractoriness in healthy human atria is preferentially voltage-dependent, rather than time-dependent. Time dependence of sodium channel recovery affects refractoriness only at pathophysiologically high activation rates. The resting membrane potential is a potential target in pharmacological management of cAF.